Effects of a Brief Meditation Training on Negative Affect, Trait Anxiety and Concentrated Attention - Menezes, Carolina Baptista; Bizarro, Lisiane (Paidéia (Ribeirão Preto), 2015)
Meditation has been associated with positive psychological outcomes, but few studies have investigated brief interventions. This randomized controlled pilot study assessed the effects of five days of focused meditation on positive and negative affect, state and trait anxiety, as well as concentrated attention in a nonclinical sample distributed in two groups (experimental = 14, 51.8% female, Mage= 23.9; control = 19, 62% female, Mage= 24.9). The instruments used were the Positive Affect and Negative Affect Scale, State and Trait Anxiety Inventory, and the Concentrated Attention Test. The meditation group reduced negative affect and trait anxiety, and also improved correct responses on the attention test, relative to controls. These preliminary findings indicate that even short focused meditation training may help improve some psychological variables. It is discussed that the early manifestation of these benefits may be especially relevant to strengthen the motivation to continue and practice regularly.